Helium Tagging Infrared Photodissociation Spectroscopy of Reactive Ions - Roithová, Jana; Gray, Andrew; Andris, Erik; Jašík, Juraj; Gerlich, Dieter (Accounts of chemical research, 2016)
The interrogation of reaction intermediates is key for understanding chemical reactions; however their direct observation and study remains a considerable challenge. Mass spectrometry is one of the most sensitive analytical techniques, and its use to study reaction mixtures is now an established practice. However, the information that can be obtained is limited to elemental analysis and possibly to fragmentation behavior, which is often challenging to analyze. In order to extend the available experimental information, different types of spectroscopy in the infrared and visible region have been combined with mass spectrometry. Spectroscopy of mass selected ions usually utilizes the powerful sensitivity of mass spectrometers, and the absorption of photons is not detected as such but rather translated to mass changes. One approach to accomplish such spectroscopy involves loosely binding a tag to an ion that will be removed by absorption of one photon. We have constructed an ion trapping instrument capable of reaching temperatures that are sufficiently low to enable tagging by helium atoms in situ, thus permitting infrared photodissociation spectroscopy (IRPD) to be carried out. While tagging by larger rare gas atoms, such as neon or argon is also possible, these may cause significant structural changes to small and reactive species, making the use of helium highly beneficial. We discuss the "innocence" of helium as a tag in ion spectroscopy using several case studies. It is shown that helium tagging is effectively innocent when used with benzene dications, not interfering with their structure or IRPD spectrum. We have also provided a case study where we can see that despite its minimal size there are systems where He has a huge effect. A strong influence of the He tagging was shown in the IRPD spectra of HCCl(2+) where large spectral shifts were observed. While the presented systems are rather small, they involve the formation of mixtures of isomers. We have therefore implemented two-color experiments where one laser is employed to selectively deplete a mixture by one (or more) isomer allowing helium tagging IRPD spectra of the remaining isomer(s) to be recorded via the second laser. Our experimental setup, based on a linear wire quadrupole ion trap, allows us to deplete almost 100% of all helium tagged ions in the trap. Using this special feature, we have developed attenuation experiments for determination of absolute photofragmentation cross sections. At the same time, this approach can be used to estimate the representation of isomers in a mixture. The ultimate aim is the routine use of this instrument and technique to study a wide range of reaction intermediates in catalysis. To this end, we present a study of hypervalent iron(IV)-oxo complexes ([(L)Fe(O)(NO3)](+)). We show that we can spectroscopically differentiate iron complexes with S = 1 and S = 2 according to the stretching vibrations of a nitrate counterion.
Keywords: Nitrates; helium; Spectrum Analysis; Iron Compounds; Catalysis; sloučeniny železa; Helium; katalýza; dusičnany; spektrální analýza